Viral-Infected Change of the Digestive Tract Microbiota Associated With Mucosal Immunity in Teleost Fish - Dong, Shuai; Ding, Li-guo; Cao, Jia-feng; Liu, Xia; Xu, Hao-yue; Meng, Kai-feng; Yu, Yong-yao; Wang, Qingchao; Xu, Zhen (Frontiers in Immunology, 2019)
The digestive tract is a unique series of organs that it is inhabited by a range of commensal microbes, while also exposed to an overwhelming load of dietary antigens. It is widely known that mammals have evolved complex and efficient immune strategies to protect the mucosa of digestive tract. However, in the early vertebrates, the roles of mucosal immune defense and microbial communities in the different segments of digestive tract are not well understood. Here, we constructed a bath infection model with infectious hematopoietic necrosis virus (IHNV) in rainbow trout (Oncorhynchus mykiss). Importantly, following viral infection, we found that the IHNV distribution and the reactions of immune-related genes had similar trends that decreased across the digestive tract. Hematoxylin and eosin (H & E) and alcian blue (A & B) staining of the trout digestive tract showed that the pathological changes only occurred in the buccal and pharyngeal mucosal tissues. Moreover, the increased diversity of the microbial community was only detected in the buccal mucosa through 16S rRNA gene sequencing suggesting that the magnitude of the immune response and microbial community changes are related to the IHNV load and the original microbial diversity. In addition, the loss of digestive tract dominant species and increased colonization of opportunistic bacteria were discovered in the buccal mucosal surface indicating that a secondary bacterial infection occurred in this mucosal tissue.